Status of Fusarium Wilt Incidence on Summer Radish and Etiological Characteristics of the Causal Fungus in Korea - Sung Kee Hong; Hyoungrai Ko; Hyo-Won Choi; Youngkee Lee; Jeomsoon Kim (Research in Plant Disease, 2020)
Incidence of Fusarium wilt was surveyed in fields of summer radish in Gangwon province in Korea in 2018 and 2019. The disease started in early July and spread rapidly in hot summer of late July and August and in severe case, reached up to 80% in a field in Gangneung area. Symptoms in the seedling stage include poor growth and browning of internal tissue of root. During mid-growth, the leaves of diseased plant turned yellow over time, the surface of the roots changed from white to blackish, and the vascular tissues turned brown. A total of 23 isolates was obtained from the diseased plants and identified as Fusarium oxysporum f. sp. raphani by elongation factor-1a and intergenic spacer sequence analysis. Pathogenicity of the isolates was tested by artificial inoculation to the radish and other plants. All the isolates tested were pathogenic to radish plant, although there were differences in virulence on radish 11 cultivars. However, the isolates were not virulent to other plants except some cruciferous vegetables including Brussels sprouts, rocket, stock, and turnip. The results of pathogenicity test showed that it is necessary to rotate with crops other than cruciferous vegetables in order to prevent Fusarium wilt from radish fields.